Bonhoeffer on Modernity: Sic et Non - Elshtain, Jean Bethke (Journal of religious ethics, 2001)
Though Bonhoeffer is usually thought to have been one of the architects of modern theology, he was also one of modernity’s most penetrating critics. The author lays out Bonhoeffer’s challenges to certain cherished modern assumptions by examining (1) his linkage of totalitarianism to the political utopianism that arose out of the French Revolution, (2) his fear of the nihilistic implications of the rationalists’ notion of the sovereign self and of the modern tendency to view life as an end in itself, and (3) his suspicion of all forms of moral absolutism, including the Kantian absolutizing of the duty to tell the truth. What emerges is a picture of Bonhoeffer as a theologian who coupled a keen sense of our creatureliness and limitation with a resolute belief in the activity of God in history, and of Bonhoeffer as an ethicist who generated a Christian relational ethics that offers an alternative to both the ethics of abstract principle and the ethics of intuitive situational response.